Legal System Transformation As A Foundation For An Inclusive And Sustainable Future In Law Enforcement That Is Responsive To Global And Local Challenges - Dinar Galuh Sangesti (Jurnal Locus Delicti, 2025)
The transformation of the legal system has become an urgent necessity in responding to the complexity of global and local challenges, including technological advancements, transnational crimes, environmental crises, and the demand for justice that is both inclusive and sustainable. Existing legal frameworks, often constrained by rigid structures and outdated norms, face limitations in ensuring responsive and adaptive law enforcement. This study aims to formulate a transformative legal system model that strengthens law enforcement practices while integrating inclusivity, sustainability, and responsiveness to diverse socio-cultural contexts. The research employs a normative juridical method supported by a comparative approach, analyzing statutory regulations, international legal instruments, and academic literature to identify relevant principles and innovative practices. The results indicate that an effective transformation requires the integration of universal human rights, the philosophical foundation of Pancasila, technology-based enforcement mechanisms, and community participation in dispute resolution. These elements collectively enhance institutional capacity, legal certainty, and public trust. In conclusion, a responsive and sustainable legal system must embrace continuous reform, promote institutional collaboration, and ensure adaptability to emerging issues, thereby establishing law enforcement as a robust pillar of justice at both national and international levels.